The Anaemias of Chronic Infections - Berk, Lionel (Department of Medicine, 2020)
The changes occurring in the red blood cells in infective illnesses are amongst the least carefully studied problems of haematology. In spite of the fact that these anaemias are extremely common, it is different to find adequate literature to make possible even a clear description of the blood picture under these circumstances.